Consider the equation \[ x^2 + x +1 = 0 \tag {1} \]

Factorizing it, we get \[ (x + \sqrt x + 1)(x - \sqrt x + 1) = 0 , \] or \[ x + 1 = \pm \sqrt x \tag {2} \]

Substituting \((2) \) into \((1) \), we get \( \sqrt x = 0 \) as a root of equation \((1) \). And the first equation does not satisfy \(x=0 \), so how is this possible?

## Comments

Sort by:

TopNewestRemember that as you manipulate equations, you may introduce extraneous roots. Do all your equations have double-sided implication signs? EG \( x = 1 \not \Leftrightarrow x^2 = 1 \). – Calvin Lin Staff · 2 months, 4 weeks ago

Log in to reply

– Shivang Gupta · 2 months, 3 weeks ago

But I've not square my function in any step to introduce any extrenious roots. I have just implied my observation of function by substituting in it.Log in to reply

For a simple example, if we wanted to solve \( x = 0 , y = 0 \), we cannot add them up and say that oh \( x+y = 0 \), and observe that \( (x,y) = (-1, 1) \) is a solution!

This is why it's important to place implication signs everwhere, to the extent that they are valid. IE

\[ x=0, y = 0 \Rightarrow x+y = 0 \Rightarrow (x,y) = (-1, 1) \]

which tells you that the final condition could have been an extraneous solution. – Calvin Lin Staff · 2 months, 3 weeks ago

Log in to reply

– Shivang Gupta · 2 months, 3 weeks ago

In the above equation I've used only one variable and I am unable to understand that if 2 things are coming out to be equal then why they can't be substituted. In the example you mentioned you took 2 variable but I used only one variable. If you do not agree with me then please indicate the step which I did wrong with proper reasoning.Log in to reply

notvice versa.Here's a ridiculous counter example to make it clearer. Suppose \( x= 1 \). Adding \( -x = - 1 \) to both sides, we get \( 0 = 0 \). Hence, this equation is always true, so \(x\) is any value.

This is why it's always important to place implication signs to illustrate the extent that they are valid. IE \( f(x) = 0 , g(x) = 0 \Rightarrow f(x) + g(x) = 0 \) but not vice versa. – Calvin Lin Staff · 2 months, 3 weeks ago

Log in to reply

Please solve the problem above and let me understand the mistake which I'm commiting. – Shivang Gupta · 3 months ago

Log in to reply